Changes in Managerial Functions in Agriculture - Berde, Csaba (Acta Agraria Debreceniensis, 2003)
Managerial activity is a process constituted by well separable functions, tasks. The functions and the content of managerial activity are influenced by several factors.This multi-sided affectedness focused our attention on the analysis of management tasks. We aimed to formulate responses for the questions how and to what extent the activities and tasks of organizations define the tasks and functions at the given organization. On the basis of interview surveys, we analyzed the following managerial tasks: functions concerning information, communication, planning, decision-making, organization, control. The interviewed had to rank the factors influencing management tasks on a scale ranging from one to five. On the basis of the activities and tasks of organizations, we defined three types. The scope of this study does not allow us to publish all the results related to the above-mentioned managerial functions, so we can only present some, which are of interest.Our findings suggest that the realization of certain management functions is influenced by several factors. Without striving for completeness, we could only evaluate 9-11 factors per function. The evaluation of information sources is considerably differentiated in terms of the activities, tasks of organizations. In the assessment of plans, the potentials for realization and repetition were judged differently, whereas non-organization changes and individual planning similarly. The findings of impact factors in decision making are largely different, as well in terms of organizational activities, but all the interviewed ranked the interests of the organization high. Analysis on control indicated that managers attributed higher importance to issues of content than to methodological ones.Our investigations follow Fayol’s classical groups based on managerial tasks. We studied the following five tasks in the process of management: information tasks, planning, decision-making, instructions and control. We performed our studies with the inclusion of agricultural organization managers, with questionnaire surveys. The interviewed were asked to qualify the impact factors on the five investigated management tasks on a scale ranging from 1-5. We identified the following company groups: small company, medium company and large company.We performed our analysis on the basis of company sizes as well, seeking to formulate responses on how size influences the qualification of the investigated factors.Our findings suggest that the interviewed company managers attribute higher than average roles to the tasks of the management process. The qualification, ranking of management tasks are considerably influenced by company sizes. Relationships and venues are important in the implementation of information tasks, whereas the viability of plans is essential in the process of planning. Usefulness and company interests are highlighted in decision-making. In the case of instructions and decision-making, we stressed the significance of content elements as opposed to formal ones.